Penile amputation in Buerger's disease - An unusual cause of organ loss - Orhan, I; Onur, R; Akpolat, N; Semercioz, A (Informa Healthcare, 2004)
We report a case of Buerger's disease in a 70-year-old man which involved the penile arterial system and subsequently led to penile amputation.
Keywords: amputation; Buerger's disease; gangrene; penis